2019
DOI: 10.1002/gps.5203
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of neuropsychiatric symptoms over time in healthy volunteers and risk of MCI and dementia

Abstract: Objectives To identify subtypes of neuropsychiatric symptom (NPS) course among cognitively normal individuals and to assess the association between these subtypes and hazard of later mild cognitive impairment (MCI) or dementia diagnosis. Methods We modeled neuropsychiatric inventory questionnaire (NPI‐Q) scores from 4184 volunteers over approximately 4 years using growth mixture models, generating latent classes of trajectory. We then fit Cox proportional hazard models to determine if membership in trajectory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Follow up of individuals in these clusters could also determine whether reduced cognitive function, as in some individuals in cluster 4, is due to cognitive impairment or to interference by high anxiety level, which was found to significantly influence membership in this cluster [ 60 ]. Indeed, recent studies have found that the presence of symptoms of mental disorders in older, cognitively unaffected people increases their risks for cognitive impairment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow up of individuals in these clusters could also determine whether reduced cognitive function, as in some individuals in cluster 4, is due to cognitive impairment or to interference by high anxiety level, which was found to significantly influence membership in this cluster [ 60 ]. Indeed, recent studies have found that the presence of symptoms of mental disorders in older, cognitively unaffected people increases their risks for cognitive impairment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical conditions in later life, especially in individuals with multimorbidity, have been closely associated with mental conditions, especially anxiety and depression, with these physical and mental conditions acting sinergistically to increase the probability of negative health-related outcomes [ 2 , 17 , 18 ]. Anxiety and depression in older people manifest as a variety of symptoms, including anxious feelings, dysphoria, apathy, worry, trouble sleeping, irritability, and fatigue [ 19 21 ]. These symptoms of anxiety and depression may overlap with each other, as well as with cognitive and physical conditions, making mental conditions more difficult to recognize in older persons, especially in primary care (PC) situations, in which patients present with different symptoms and morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The following exclusions were applied: (1) treatment with an FDA-approved medication for AD; (2) presence of a psychiatric disorder diagnosed on clinical basis; (3) treatment with hypnotic, antipsychotic, sedative or anxiolytic drugs. The rational for these exclusions was to avoid potential confounding effects of these conditions on cognitive performance [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is reasonable to mention that a group of individuals with neuropsychiatric symptoms does not progress to dementia, keeping up a relatively stable cognitive trajectory. In a 4‐year follow‐up of individuals with NC, Leoutsakos et al 65 . found that 16% of them, with neuropsychiatric symptoms treated with antidepressants and additional procedures, achieved a favourable trajectory over this period.…”
Section: Discussionmentioning
confidence: 99%